Konsep Harmoni Pata Dela Orang Bajawa: Implikasinya dalam Pembentukan Integritas Akademik di Perguruan Tinggi - Bito, Gregorius Sebo; Hawali, Rebeka Filda; Sutajaya, I Made; Suja, I Wayan; Astawa, Ida Bagus Made (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2024)
This study aims to discuss the concept of harmony from the pata dela of the Bajawa people and its implications for forming academic integrity in higher education. In Indonesia's higher education context, technological advancements and changes in teaching methods have increased the potential for academic dishonesty. Pata dela, which consists of ancestral teachings from the Bajawa people, contains moral values that can contribute to supporting academic integrity. Through a qualitative approach, this research explores how the values from pata dela can be integrated into the higher education curriculum to create a supportive learning environment for academic integrity. The research findings indicate that values like honesty, trust, fairness, respect, and responsibility embedded in pata dela can help prevent academic misconduct and foster a culture of integrity among students and faculty. The research results can be implemented in higher education as a preventive effort to prevent academic disintegrity through habituation based on local wisdom.